Love in The Short Story “Hilm Sa‘ah” By Naguib Mahfouz: An Analysis of The Inner Structure By I.A. Richards (Structuralist Study) - Efendi, Syarah Ananda; Rasyad, Rasyad; Fajri, Akmal (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
This study analyzes the inner structure of love in the short story Hilm Saʿah by Naguib Mahfouz using the theory of I.A. Richards. The problem of this research focuses on how language constructs the inner emotional experience of love through the elements of sense, feeling, tone, and intention. The aim of this study is to describe and analyze the dynamics of love as an inner phenomenon formed through linguistic meaning and narrative expression. This research employs a descriptive qualitative method with close reading techniques, using the short story as the primary data source. The analysis is conducted by identifying and interpreting the four elements of inner structure to reveal how emotional meaning is developed in the text. The findings show that love is constructed as an imaginative and psychological experience shaped by the character’s inner condition, particularly loneliness, desire, and emotional needs. The emotional dynamics develop from fascination and happiness to anxiety and ultimately disappointment. In conclusion, love in this short story is represented as a temporary and illusory experience; however, it produces a deep emotional and existential impact through the interaction between language and the character’s inner consciousness.